Three-dimensional characterization of superplastic grain boundary sliding inside Al–Zn–Mg–Cu alloy sheet. (15th April 2019) - Masuda, Hiroshi; Tobe, Hirobumi; Hara, Toru; Sato, Eiichi
Abstract: Grain boundary sliding (GBS) and grain rotation, the predominant mechanisms of superplasticity, were three-dimensionally characterized inside 7475 aluminum alloy (Al–Zn–Mg–Cu) by combining internal oxide markers and three-dimensional (3D) electron backscatter diffraction (EBSD). The internal oxide markers were introduced via hot press bonding of two alloy sheets, hot rolling, cyclic cold rolling, and recrystallization by heat treatments. The microstructures after superplasticity at 500 °C and 2 × 10 −4  s −1 was observed by 3D–EBSD combined with focused ion beam. The 3D–EBSD tomography successfully reconstructed GBS and grain rotation in three dimensions with crystal orientation informations during superplasticity. Graphical abstract: Unlabelled Image